2000
DOI: 10.1162/089892900562309
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Segmentation in Phonological Processing: An fMRI Investigation

Abstract: Abstract& Phonological processes map sound information onto higher levels of language processing and provide the mechanisms by which verbal information can be temporarily stored in working memory. Despite a strong convergence of data suggesting both left lateralization and distributed encoding in the anterior and posterior perisylvian language areas, the nature and brain encoding of phonological subprocesses remain ambiguous. The present study used functional magnetic resonance imaging (fMRI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
266
3
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 347 publications
(303 citation statements)
references
References 40 publications
31
266
3
3
Order By: Relevance
“…The present study observed significant increases in left IFG activation when participants discriminated the initial consonant of a syllable pair, consistent with results from other studies finding activation in this region during speech discrimination, phoneme monitoring, and rhyme monitoring (Binder et al, 1997;Burton et al, 2000;Demonet et al, 1992;Zatorre et al, 1992). Nevertheless, the exact role that left IFG plays in these types of tasks remains controversial (Poeppel, 1996).…”
Section: Inferior Frontal Gyrussupporting
confidence: 90%
See 1 more Smart Citation
“…The present study observed significant increases in left IFG activation when participants discriminated the initial consonant of a syllable pair, consistent with results from other studies finding activation in this region during speech discrimination, phoneme monitoring, and rhyme monitoring (Binder et al, 1997;Burton et al, 2000;Demonet et al, 1992;Zatorre et al, 1992). Nevertheless, the exact role that left IFG plays in these types of tasks remains controversial (Poeppel, 1996).…”
Section: Inferior Frontal Gyrussupporting
confidence: 90%
“…One possibility is that left IFG is involved in accessing higher-order phonological representations such as articulatory gestures and that superior temporal regions are responsible for accessing more basic characteristics of speech such as phonetic features. Burton et al (2000) tested this theory using an auditory speech discrimination task and fMRI. In one experiment, participants were asked to judge whether a pair of otherwise identical words had the same initial phoneme (e.g., tip-tip vs tip-dip); the second experiment was similar except that stimulus words differed in terms of several phonemes not involved in discrimination (tip-tomb vs tip-doom).…”
Section: Inferior Frontal Gyrusmentioning
confidence: 99%
“…Thus, switching between the two conditions could have enhanced cognitive demands causing an increase of the frontal activation in both conditions. Enhanced activation of the left IFG with increasing computational demands in a phoneme monitoring task (Demonet, Price, Wise, & Frackowiak, 1994) and in a phonological discrimination task (Burton, Small, & Blumstein, 2000) was previously shown. Therefore, the left accentuated frontal activation pattern in prosodic speech might reflect the effort to discriminate phonological aspects in different auditory modes, as the main difference between normal and prosodic speech is speech intelligibility.…”
Section: Frontal Activationmentioning
confidence: 73%
“…Following 2 Burton et al (2000) observed a left inferotemporal activation (TC À58, À56, À8) when subjects performed same -different judgments on spoken syllables, but only when they had to extract the first phoneme of the syllable, not when they could base their decisions on the syllable as a whole. This region, which is ascribed to the inferior temporal gyrus, seems to be more lateral than the VWFA.…”
Section: Functional Specializationmentioning
confidence: 95%